Pengaruh Pemberian Senam Hamil Terhadap Peningkatan Kapasitas Vital Paru Pada Ibu Hamil (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2008)
This watchfulness aims to detect pregnant gymnastics gift influence towards vital capacity enhanced lung. this watchfulness is carried out at Jakarta Islamic Hospital in July to september month 2006. Sample numbers 15 pregnant womans, with age esti-mate between 19-36 year. Has quasi experimental to detect influence a intervention or treatment in watchfulness object. Technics taking sample done technicsly purposive sampling. To see vital capacity enhanced lung is used measuring instrument spirometri. processing and data analysis menguna statistical program for social science (spss verse 13). Researcher concludes that there is pregnant gymnastics gift influence towards vital capacity enhanced paru in pregnant mother. This conclusion is based on result data testing with test t-test related that is p< Î±. based on hypothesis testing result on so got value p= 0.000 that demo that there is influence significant pregnant gymnastics practice gift towards enhanced vital lung in this matter pregnant mother is caused because inspiration ability magnitude and produce ventilation alveolar better. Thereby pregnant gymnastics very good is done in pregnant mother.Â Keywords: Pregnant Gymnastics, Vital Lung, Ventilation